Destabilization of DNA through interstrand crosslinking by UO22+. Issue 14 (15th January 2019) - Rossberg, André; Abe, Takaya; Okuwaki, Koji; Barkleit, Astrid; Fukuzawa, Kaori; Nakano, Tatsuya; Mochizuki, Yuji; Tsushima, Satoru
Abstract : UO2 2+ was shown to form an interstrand crosslink between two different strands of a single DNA molecule. Abstract : UO2 2+ was shown to form an interstrand crosslink between two different strands of a single DNA molecule. This crosslink hardly affected the hydrogen bonds between nucleobase pairs but destabilized the π–π stacking between the two nucleobases in the vicinity of UO2 2+ -bound phosphate. Thereby, the fragility of the DNA backbone increased upon UO2 2+ binding.